Biochar Production From Vineyard Pruning Waste by Oxidative Torrefaction - Ozer, Gizem; Duranay, Neslihan (Wiley, 2025)
The torrefaction process for producing biochar from waste biomass has garnered significant attention in recent years. However, economic constraints hinder the broader adoption of this process. One such constraint is the requirement for an inert atmosphere during torrefaction. This study aimed to evaluate the feasibility of torrefying vineyard pruning waste in an oxygen-rich environment. Torrefaction of waste vine shoots was conducted in a fixed-bed reactor, utilizing a carrier gas medium with varying O-2 concentrations (0% to 21%) at process temperatures of 220 degrees C, 250 degrees C, and 280 degrees C. Proximate and elemental analyses revealed that the torrefaction temperature is the key variable influencing biochar yield. Moreover, under mild torrefaction conditions, an increase in the carrier gas O-2 concentration had a lesser impact on product yield compared with process temperature. Thus, it can be inferred that combustion gases and gases generated under mild torrefaction conditions could serve as carrier gases for a more cost-effective torrefaction process. Under oxidative conditions, the total biomass energy recovery was measured at 87.3% +/- 1.7% for low temperatures and short torrefaction durations.
Keywords: agricultural waste; biochar; energy yield; feasibility of torrefaction; higher heating values; oxidative torrefaction; vineyard purping